Chronic Jet Lag Exacerbates Jejunal and Colonic Microenvironment in Mice - Li, Qing; Wang, Bo; Qiu, Hong-Yi; Yan, Xiu-Juan; Cheng, Li; Wang, Qian-Qian; Chen, Sheng-Liang (Frontiers in Cellular and Infection Microbiology, 2021)
Background and objective Intestinal diseases caused by circadian rhythm disorder are a leading health concern worldwide. Experimental evidence from the past years highlights a key role for the circadian rhythm in maintaining the homeostasis of intestinal flora and host health. This study aimed to systematically describe the microbiota disorder of the whole intestine, including jejunum and colon, caused by jet lag (JL). It also focused on fecal metabolomics to find out meaningful metabolites in the long-term jet-lagged mice. Method A mouse model was built to mimic the situation of shift workers under chronic JL. The mice were kept under strict light–dark conditions. For the normal-rhythm group, lights were turned on at 6 a.m. and turned off at 6 p.m. On the contrary, jet-lagged mice were subjected to an 8-h light cycle in advance, kept under these conditions for 3 days, and then reverted to the original light–dark cycle. After another 3 days, this pattern was repeated. Finally, six normal mice and five mice after 4-month JL were euthanized. The microbiota of fecal samples and jejunal contents were analyzed by 16S ribosomal RNA gene sequencing. Also, fecal metabolomics was used to explore the differences between the jet-lagged group and the normal one. Results A long-term JL could decrease the richness and diversity of gut microbiota in both the colon and jejunum. The results of 16s RNA sequencing showed that circadian rhythm disorders had a greater impact on the jejunal microbiome. Besides changes in gut microbiota, the metabolomics of fecal samples showed that the levels of tryptophan and indole derivatives decreased after 4-month JL. The levels of short-chain fatty acids did not change in the JL group. Other metabolites that attracted attention included itaconic and bile acids. Conclusions This study presented a comprehensive landscape of gut microbiota and their metabolites in mice experiencing circadian rhythm disturbances. It suggested that the long-term circadian rhythm disorder led to a dysbiosis of the gut microenvironment. It provided evidence to set up a chain of “JL–gut microbiome–intestinal diseases.”